2017
DOI: 10.1002/ejp.1119
|View full text |Cite
|
Sign up to set email alerts
|

New approach for the treatment of neuropathic pain: Fibroblast growth factor 1 gene‐transfected adipose‐derived mesenchymal stem cells

Abstract: AD-MSCs attenuated the CCI-induced mechanical and thermal hypersensitivity. Spinal structural alterations and apoptosis were significantly decreased in the AD-MSCs group. Elevated levels of FGF1 were detected in the spinal tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 90 publications
1
37
0
1
Order By: Relevance
“…After mounting, a 5 μm section of each tissue was prepared and then stained with H&E. Histopathological changes were then investigated and blindly scored by a pathologist. 21,22…”
Section: Histopathological Examinationmentioning
confidence: 99%
“…After mounting, a 5 μm section of each tissue was prepared and then stained with H&E. Histopathological changes were then investigated and blindly scored by a pathologist. 21,22…”
Section: Histopathological Examinationmentioning
confidence: 99%
“…Studies have shown that fibroblast growth factor (38,39) and hepatocyte growth factor (40,41) can reduce pain by inhibiting the activation of astrocytes in the spinal cord; and PRP contains various growth factors, including fibroblast growth factor and hepatocyte growth factor (42), so a longterm higher concentration of PRP acts on cells or may make such inhibitory effects more obvious Traditional studies have suggested that peripheral and central sensitization causes chronic pain due to changes in neuronal plasticity. However, recent studies have found that glial cells, especially astrocytes, play an essential role in maintaining chronic pain (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…The experimental n was determined based on previous literature data [23,39,40]. The n per group is indicated in legends.…”
Section: Ethical Concernsmentioning
confidence: 99%
“…The CCI animals received SCAP topically (10 6 cells reconstituted in 200 mL of PBS; treated group), or 200 mL of PBS (control group) at the surgery site, around the sciatic nerve on day 0. The dose and route of administration of SCAP were determined based on prior publications [22][23][24][25]. Mechanical hyperalgesia, radiant heat hyperalgesia, and cold allodynia were assessed before (day -3; basal) and at days 3, 7, 14, and 21 after surgery.…”
Section: Neurite Quantificationmentioning
confidence: 99%
See 1 more Smart Citation